The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-022-35259-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical-resolution functional gastrointestinal photoacoustic endoscopy based on optical heterodyne detection of ultrasound

Abstract: Photoacoustic endoscopy shows promise in the detection of gastrointestinal cancer, inflammation, and other lesions. High-resolution endoscopic imaging of the hemodynamic response necessitates a small-sized, high-sensitivity ultrasound sensor. Here, we utilize a laser ultrasound sensor to develop a miniaturized, optical-resolution photoacoustic endoscope. The sensor can boost the acoustic response by a gain factor of ωo/Ω (the frequency ratio of the signal light and measured ultrasound) by measuring the acousti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The energy transduction coefficient of the two US sensors was also estimated by considering their thin-film characteristics. The developed needle US sensor exhibited a higher value, suggesting a more efficient energy conversion and superior performance, as shown in Table 1 2 , 10 …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The energy transduction coefficient of the two US sensors was also estimated by considering their thin-film characteristics. The developed needle US sensor exhibited a higher value, suggesting a more efficient energy conversion and superior performance, as shown in Table 1 2 , 10 …”
Section: Methodsmentioning
confidence: 98%
“…The developed needle US sensor exhibited a higher value, suggesting a more efficient energy conversion and superior performance, as shown in Table 1. 2,10 We performed hydrophone directivity measurements to evaluate the effects of the incident angle of US waves originating from different scan points. The experimental results indicate that the detected amplitudes can be maintained at >90% levels from the peak values for incident angles in the AE5 deg range [Fig.…”
Section: Methodsmentioning
confidence: 99%
“… 18 PA endoscopy (PAE) is essentially a variant of PAM, grounded in the same principles. However, it typically incorporates a compact probe and captures PA images through rotational scanning 19 or MEMS mirror scanning. 20 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several different optical ultrasound sensors have been explored in PA imaging. 19 , 25 , 26 Their main advantages include wide bandwidth, low electromagnetic interference, and high sensitivity per unit area. 27 32 These optical ultrasound sensors have undergone significant development, especially fiber laser sensor that has not been elaborated upon in detail in existing reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Guan Baiou et al reported a photoacoustic imaging application of fiber laser bent into different diameters to achieve ultrasonic response with different spatial resolution [ 15 ]. In 2022, Guan’s team developed a miniaturized photoacoustic endoscope system with a noise equivalent pressure density (NEPD) below 1.5 mPa/Hz 1/2 and a measurement range from 5 to 25 MHz [ 16 ]. As a highly sensitive candidate, the DBR fiber laser is also promising for marine applications such as pressure, tsunami, and earth dynamics [ 17 ].…”
Section: Introductionmentioning
confidence: 99%